Estimation of Soil Material Transportation by Wind Based on in Situ Wind Tunnel Experiments - Farsang, Andrea; Duttmann, Rainer; Bartus, Máté; Szatmári, József; Barta, Károly; Bozsó, Gábor (Journal of Environmental Geography, 2013)
25% and 40% of territory of Hungary is moderate to highly vulnerable to deflation. However, precise estimates about the soil loss and related losses of organic matter and nutrients due to wind erosion are missing in most cases. In order to determine magnitudes of nutrient masses removed at wind velocities that frequently occur in SE Hungary, in-situ experiments using a portable wind tunnel have been conducted on small test plots with an erosional length of 5.6 m and a width of 0.65 m. The wind tunnel experiments have been carried through on a Chernozem which is typical for this region. In order to compare the effects of soil coverage on the masses of blown soil sediment and adsorbed nutrients, two soil surface types have been tested under similar soil moisture und atmospheric conditions: (1) bare soil (dead fallow) and (2) bare soil surface interrupted by a row of maize plants directed downwind along the center line of the test plots. The results of our experiments clearly show that a constant wind velocity of 15 m s-1 (at a height of 0.3 m) lasting over a short time period of 10 minutes can already cause noticeable changes in the composition and size of soil aggregates at the top of the soil surface. Due to the grain size selectivity of the erosive forces the relative share of soil aggregates comprising diameters > 1 mm increased by 5-10% compared with the unaffected soil. Moreover it has shown that short time wind erosion events as simulated in this study can result in erosion rates between 100 and 120 g m-2, where the erosion rates measured for bare soils are only slightly, but not significantly higher than those of the loosely vegetated ones. Soil samples taken from sediment traps mounted in different heights close to the outlet of the wind tunnel point to an enrichment of organic matter (OM) of about 0.6 to 1 % by mass referred to the control samples. From these findings has been calculated that the relocation of organic matter within short term wind erosion events can amount to 4.5 to 5.0 g OM m-2. With the help of portable field wind tunnel experiments we can conclude that our valuable, high quality chernozems are struck by wind erosion mainly in drought periods.